Shareholder Value of the Company and Financial Statements: Econometric Estimation of Value Creation Drivers - Kadochnikova, E.; Usanova, D.; Zulfakarova, L.; Drozdova, D. (International Journal of Criminology and Sociology, 2022)
In this work to evaluate the relationship between financial reporting indicators and shareholder value on the example of the Russian companies from seven sectors of the economy linear multiple regression model and classical least squares methods has been used. The results depict that it is expected that financial reporting indicators are one of the dominant determinants of evaluating the effectiveness of financial investment decisions. Also, it is shown that the financial drivers-financial leverage, return on assets, dividend payments, and the EVA driver – invested capital-are positively correlated with the company’s shareholder value. The results represent that the size of a company has a positive impact on its shareholder value. It was found that the level of disclosure is negatively correlated with the company’s shareholder value. Due to the fact that the article uses data from the financial statements of the 85 Russian companies for 2018 to measure the relationship between three groups of drivers and the company’s shareholder value is an innovative work that can be used in scientific and practical activities by owners and investors of companies in order to improve the financial reporting of companies and make investment decisions.